The association between physical fitness level with anthropometric indicator and body compositions among older adults with possible sarcopenia and sarcopenia in Kelantan - Yu, Lourna Tang Sing (Universiti Sains Malaysia, 2024)
The aging process involves changes in physiological systems, such as the loss of lean body mass (mainly muscle) and decreased muscular strength and function known as sarcopenia, a new geriatric syndrome. Sarcopenia significantly impacts healthcare by leading to decreased bone mineral density, increased fall risk, reduced functional ability, greater physical dependence, and higher mortality rates in older adults. The aim of this study was to explore the relationship between physical fitness level (gait speed and chair sit-and-reach test) with anthropometric indicator (waist circumferences, hip circumferences, mid-upper arm circumferences, waist-to-hip-ratio, body-mass index and calf circumference) and body composition (fat mass, visceral fat and skeletal muscle) among older adults with possible sarcopenia and sarcopenia. A cross-sectional study was conducted among 92 elderly aged 60 years old and above using convenience sampling technique in Kelantan. Short physical performance, handgrip strength and skeletal mass index were used to determine sarcopenia status during interview session. Socio-demographic background, anthropometric indicator, body composition and physical fitness level were also included during the interview. Among the physical fitness measures, only gait speed (p-value= 0.007) showed a significant relationship with elderly with sarcopenia and possible sarcopenia while the chair sit-and-reach test (p-value= 0.841) did not. Anthropometric indicator did not show a significant relationship with chair sit-and-reach test. Regarding body composition, fat mass showed a positive and moderate relationship with gait speed (r= 0.354, p-value= 0.001). Nonetheless, it is suggested future intervention studies should be carried out to determine the effectiveness of structured exercise programme for sarcopenia.